An Improved Process Towards Hexahydro‐1, 3, 5‐trinitroso‐1, 3, 5‐triazine (TNX). Issue 2 (13th January 2017) - Rothstein, Sarah A.; Dubé, Pascal; Anderson, Stephen R.
Abstract: Hexahydro‐1, 3, 5‐trinitroso‐1, 3, 5‐triazine (TNX) is mostly known as a by‐product in the environmental decomposition of RDX. The original chemistry to TNX was never optimized and thus resulted in low yields due to competitive degradation of the starting material. Enabled conditions to TNX were developed by optimizing pH effects and mitigating foaming by reactor geometry and stirring. The conditions presented herein allow for the inexpensive and simple production of multi‐gram quantities of TNX. The isolated TNX obtained by our new method was characterized by 1 H NMR, 13 C NMR, DSC, and X‐ray crystallography. A preliminary evaluation of the sensitivity of TNX towards impact and friction is also presented. Abstract :